The Quest for Caribbean Identities: Postcolonial Conflicts and Cross-Cultural Fertilization in Derek Walcott’s Poetry (AmeriQuests, 2010)
ABSTRACT: This paper investigates how the political merges with the literary in Derek Walcott’s poetry, using the poems “A Latin Primer” and “The Light of the World” as primary examples. In these two poems, Walcott explores the colonial wounds of the Caribbean region and the various consequences of colonialism for the forging of Caribbean’s contemporary identities. He proposes a model of Caribbeanness that values racial multiplicity and cross-dialogues between cultures, including, perhaps problematically, the European cultural tradition, as fertilizing. For Walcott, poetic creativity serves to truly unify and find points of connections in a disjointed postcolonial world. This paper examines the implications of Walcott’s stances on postcolonial identity politics and compares Walcott to several French Caribbean authors.RÉSUMÉ: Cet article explore comment la polique et la littérature fusionnent dans la poésie du Prix Nobel de Littérature Derek Walcott, utilisant les poèmes “A Latin Primer” et “The Light of the World” comme exemples principaux. Dans ces deux poèmes, Walcott analyse les blessures coloniales encourues par les Antilles et les différentes conséquences du colonialisme pour la création des identités antillaises contemporaines. Il propose un modèle d’antillanité qui célèbre la multiplicité raciale et les dialogues fertilisateurs entre les cultures, y compris la culture européenne, donnant peut-être ainsi matière à controverse. Pour Walcott, la créativité poétique sert à unifier et connecter un monde postcolonial disjoint. Cet article examine les différentes implications des positions de Walcott concernant les politiques d’identités postcoloniales et compare Walcott à certains auteurs des Antilles francophones.